Concept Process with Mathematical Thinking Tools under the Domain of Piaget’s Theory of Cognitive Development - Muhammad Khalil, Zahoor-ul-Haq (JCTE, 2023)
Mathematical thinking is the habit of mind. It is important for school as it activates and regulates thinking that is essential for conceptual learning. Although, mathematics’ educationists are undivided in this that conceptual learning is a tough cognitive activity and uncontroversial aim of mathematics educ